Multicenter evaluation of the IL‐3‐pSTAT5 assay to assess the potency of cryopreserved stem cells from cord blood units: The BEST Collaborative study. Issue 8 (30th June 2022) - Trépanier, Patrick; Fournier, Diane; Simard, Carl; Fontaine, Magali J.; Stroncek, David; Takanashi, Minoko; McKenna, David; Schwartz, Joseph; Tanhehco, Yvette C.; Reems, Jo‐Anna; Torrents, Silvia; Kogler, Gesine; et al.
Abstract: Background: The IL‐3‐pSTAT5 assay, a new, rapid, and standardized flow‐cytometry‐based assay may compensate for several limitations of the colony‐forming unit (CFU) assay typically used for stem cell potency assessments of cord blood units (CBU). We performed an inter‐laboratory evaluation of the performance of this new assay. Study design and methods: This Biomedical Excellence for Safer Transfusion (BEST) Collaborative multicenter, international study included 15 participants from public cord blood banks (CBBs), CBB‐supporting research laboratories, and stem cell laboratories. To perform the IL‐3‐pSTAT5 assay, participating centers received reagents, instructions, and 10 blind CBU samples, including eight normal samples and two samples exposed to a transient warming event. We measured inter‐laboratory agreement qualitatively (proportion of correctly classified samples) and quantitatively (coefficient of variation [CV], correlation coefficients, receiver operating characteristics (ROC) curve, and intraclass correlation coefficient [ICC]). Results: The qualitative agreement was 97.3% (i.e., 107/110; Fleiss' kappa = 0.835). The average CV on a per‐sample basis was 11.57% among all samples, 8.99% among normal samples, and on a per‐center basis was 9.42% among normal samples. In a correlation matrix that compared results across centers, the mean Pearson's correlation coefficient was 0.88 (standard deviation = 0.04). The ICC was 0.83 (95% confidence interval = 0.68–0.95). The area under the curve (AUC) from the ROC curve was 0.9974. Discussion: Excellent qualitative and quantitative agreement was exhibited across laboratories. The IL‐3‐pSTAT5 assay may therefore be implemented in flow cytometry laboratories to rapidly and reliably provide standardized measures of stem cell potency in CBUs.